Uso de aplicaciones tecnológicas en agencias de viajes para la comercialización de productos turísticos en Manabí - Franco Romero, José Daniel (2021)
The main objective of this research was to determine the use of technological applications for the commercialization of tourist products in Manabí, which presents three phases: the first phase of the investigation allowed the characterization of travel agencies, where it was observed how they are distributed, this It was carried out through a cadastre of Ecuador's travel agencies, later the synthetic analytical method was used to have a more developed idea of the agencies. In the second phase, the use of ICT for supply and demand was determined, an analysis of the tourism product and service consumption was carried out, resulting in the agencies working to improve the reception they have in the market, in addition to the strategies marketing and marketing channels they have within planning. By identifying the different types of ICT used, a characterization of information technologies was carried out, to have a database on the main technologies used by travel agencies. As a final phase, an evaluation of the six agencies was made to know the adequate management of ICTs, resulting in the experts performing well with the use of these technological tools. The conclusions of the research approve that, in addition to the use of social networks, they also use web pages and SEM, which is the paid search process and organic search SEO, as the main engine to reach customers.